Constituição do complexo agroindustrial da soja no sudoeste de Goiás - Lunas, Divina Aparecida Leonel (2001)
This dissertation had as main objective to apprehend the constitution of the agroindustrial soy complex in the Southwest of Goiás Microregion. Sojiculture in Brazil has a high technological standard and a growing integration with the downstream and upstream sectors. In the region it is clear that the downstream sector has better integration and organization with the agricultural sector, and one of the movements that has become common is the partnership as a way for agro-industries to ensure specificities of the raw material. In an attempt to verify the soybean farmer's profile, a field survey was conducted in the main soybean producing municipalities in the region. The data found were crossed and analyzed together with the information obtained in the field research done in the region's agro-industries. With the data obtained, it can be noted that CAI-soy analysis has to be done using a new theory. In this dissertation, the theory that gave the theoretical support to understand the strategies detected in agribusiness was the Transaction Cost Theory. The agribusiness in the region has been trying to meet the demands of the international market, ensuring a growing consumer market, mainly European. Given the results obtained, it is understood that CAI-Soy in the region has been attracted by the physical resources, infrastructure and tax incentives that have been provided to agro-industrial complexes not only for soybeans, but also for pigs and poultry, as well as tomato. It has a strong competitiveness and may even have higher growth rates if the advantages of the region with more efficient transport infrastructure are strengthened.